Pediatric Pituitary Pituicytoma: A Case Report of Comprehensive Management - Noushin Saleki; Kazem Anvari; Hamidreza Hashemian (Middle East Journal of Cancer)
Pituicytoma, originated from pituicyte cells, is a rare pituitary tumor, especially in children. In 2007, this tumor was classified by WHO as grade 1 central nervous system tumors. The symptoms of this tumor can be headache, visual or endocrine disorders. Diagnosis is made through imaging and further confirmed by pathology and immunohistochemistry. Treatment is based on surgery, which can be risky due to the proximity to important organs and can also be accompanied by extensive bleeding. Given the low prevalence of the disease and the lack of sufficient information about the treatment of this disease, it is necessary to report the treatments performed in the existing cases to complete the evidence. We present the case of a 9-year-old boy who initially presented with headache and blurred vision, leading to the discovery of pituitary pituicytoma. This rare tumor necessitated a multidisciplinary approach involving neurosurgery and subsequent radiotherapy due to residual tumor presence post-surgery. This case highlights the challenges in diagnosis, surgical intervention, and long-term management of pediatric pituitary pituicytomas.